Akibat Hukum Terhadap Minuta Akta Sebagai Protokol Notaris Yang Musnah Dalam Penerbitan Salinan Akta - Yanti Taslim (Officium Notarium, 2021)
This study aims to determine the validity of copies of the deed issued from the perished Minute of the Deed and the legal consequences of the perished minutes in the issued copies of the deed. This is a normative legal research which uses statutory and concept approaches. The data collection was done through literature study and the secondary data were analyzed in an interpretative, deontic, and qualitative way. The results of the study concluded that, a copy of the deed remains valid if it is issued a day before the Minutes of Deed are perished and if the copy is published after the Minutes of Deed are perished through a court decision. A copy of the Deed which is issued a day after the Minutes of Deed is perished without going through the court is considered invalid. If the Minutes of Deed are destroyed due to force majeure, such as a building fire or flood, the Notary cannot be held responsible as it is beyond their control. If the Minutes of Deed are destroyed due to negligence or mistakes of the Notary, the Notary must compensate the losses incurred to the parties and/or receive administrative sanctions. A notary can take legal action to request a court order or suggest the parties to make a new deed whose contents also explain the revoking of the old deed that was destroyedKey Word:Legal Consequences, Minutes of Deed, Destruction AbstrakPenelitian bertujuan untuk mengetahui keabsahan salinan akta yang diterbitkan dari minuta akta yang musnah dan akibat hukum terhadap minuta akta yang musnah dalam salinan akta yang diterbitkan. Jenis penelitian hukum normatif dengan pendekatan undang-undang dan pendekatan konsep. Pengumpulan data dengan studi pustaka. Data sekunder dianalisa secara intepretatif, deontik, dan kualitatif. Hasil penelitian menyimpulkan, Salinan Akta tetap sah apabila diterbitkan pada tanggal 2 sebelum Minuta Akta musnah pada tanggal 3 dan apabila salinan tersebut terbit setelah Minuta Akta musnah melalui mekanisme penetapan pengadilan. Salinan Akta yang terbit pada tanggal 3 setelah Minuta Akta musnah pada tanggal 2 tetapi tanpa melalui mekanisme penetapan pengadilan dianggap tidak sah. Apabila Minuta Akta musnah disebabkan force majeur seperti kebakaran gedung atau banjir maka Notaris tidak dapat dimintai pertanggungjawaban sebab di luar kuasanya. Apabila Minuta Akta musnah akibat kelalaian atau kesalahan Notaris maka Notaris harus mengganti kerugian yang ditimbulkan kepada para pihak dan/atau mendapat sanksi administrasi. Notaris dapat melakukan upaya hukum memohon penetapan pengadilan atau menyarankan pada para pihak untuk membuat akta baru yang isinya turut menerangkan mencabut akta lama yang musnah.Kata-kata Kunci:Akibat Hukum, Minuta Akta, Musnah